2013
DOI: 10.2527/jas.2013-6445
|View full text |Cite
|
Sign up to set email alerts
|

Thermal manipulation of the embryo modifies the physiology and body composition of broiler chickens reared in floor pens without affecting breast meat processing quality1

Abstract: Selection in broiler chickens has increased muscle mass without similar development of the cardiovascular and respiratory systems, resulting in limited ability to sustain high ambient temperatures. The aim of this study was to determine the long-lasting effects of heat manipulation of the embryo on the physiology, body temperature (Tb), growth rate and meat processing quality of broiler chickens reared in floor pens. Broiler chicken eggs were incubated in control conditions (37.8°C, 56% relative humidity; RH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
95
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 61 publications
(70 reference statements)
16
95
3
1
Order By: Relevance
“…Of the three body areas analysed, the shank surface temperature may be a reliable trait for introduction of heat dissipation ability in selection programmes. The heritability values obtained in this study for body surface temperatures are consistent with the previous estimates of 0.06 to 0.19 for internal body temperature (Tixier-Boichard et al, 1995;Loyau et al, 2013) in broilers and adult layers and with those obtained for comb surface temperature in broilers (0.12 at thermo-neutrality and 0.33 in hot conditions, Loyau et al, 2013). Tixier-Boichard et al (1995) found much higher heritability of internal temperature in adult males than in females (0.49 ± 0.03 v. 0.19 ± 0.02), which suggests that measurement of temperature in adult females can be affected by daily variations due to the ovulatory cycle.…”
Section: Discussionsupporting
confidence: 80%
“…Of the three body areas analysed, the shank surface temperature may be a reliable trait for introduction of heat dissipation ability in selection programmes. The heritability values obtained in this study for body surface temperatures are consistent with the previous estimates of 0.06 to 0.19 for internal body temperature (Tixier-Boichard et al, 1995;Loyau et al, 2013) in broilers and adult layers and with those obtained for comb surface temperature in broilers (0.12 at thermo-neutrality and 0.33 in hot conditions, Loyau et al, 2013). Tixier-Boichard et al (1995) found much higher heritability of internal temperature in adult males than in females (0.49 ± 0.03 v. 0.19 ± 0.02), which suggests that measurement of temperature in adult females can be affected by daily variations due to the ovulatory cycle.…”
Section: Discussionsupporting
confidence: 80%
“…Yolk THs enter the ovum from the female circulation and are assumed to reflect circulating THs (although possibly with some control, suggested by their nonlinear correlation; McNabb and Wilson, 1997;. There is evidence for heritability of thyroid function and circulating TH levels in adult vertebrates, including chickens (for example, McLachlan et al, 2011;Loyau et al, 2013). Thus it remains an open question whether heritability of yolk THs simply reflect consistent variation in female circulating T3 levels, or whether yolk T3 levels can evolve independently.…”
Section: Discussionmentioning
confidence: 99%
“…The longer period of development and maturation of thermoregulatory mechanisms, including the hypothalamus-pituitary-thyroid and -adrenal axes, has recently been proposed as the critical period for TM to achieve efficient thermotolerance 2009a). Results obtained from Cobb broiler chickens Loyau et al, 2013) indicated that the critical period for improvement of thermotolerance is between days E7 and E16 of embryogenesis, a period which covers the setting up of both regulatory axes. TM during this period has a long-lasting positive effect on body temperature until day 70 of age (Piestun et al, 2013a), resulting in improvement in thermal resistance by reducing mortality during heat challenge by 50% in male chickens .…”
Section: Early Tm Of Poultry Speciesmentioning
confidence: 99%
“…Second, the level of increase in incubation temperature during embryogenesis has to be accurately tuned. Thermal treatment during incubation of eggs has in many studies been based on repeated increases in incubation temperature up to 39.5°C to improve thermotolerance (v. 37.8°C; Moraes et al, 2004;Collin et al, 2007;Piestun et al, 2008;Loyau et al, 2013). A treatment temperature of 41°C appeared to be too high to maintain hatchability as good as in controls (Yahav et al, 2004a).…”
Section: Early Tm Of Poultry Speciesmentioning
confidence: 99%
See 1 more Smart Citation